Would banning atrazine benefit farmers?. (January 2014) - Ackerman, Frank; Whited, Melissa; Knight, Patrick
Abstract : Atrazine, an herbicide used on most of the US corn (maize) crop, is the subject of ongoing controversy, with increasing documentation of its potentially harmful health and environmental impacts. Supporters of atrazine often claim that it is of great value to farmers; most recently, Syngenta, the producer of atrazine, sponsored an "Atrazine Benefits Team" (ABT) of researchers who released a set of five papers in 2011, reporting huge economic benefits from atrazine use in US agriculture. A critical review of the ABT papers shows that they have underestimated the growing problem of atrazine-resistant weeds, offered only a partial review of the effectiveness of alternative herbicides, and ignored the promising option of non-chemical weed management techniques. In addition, the most complete economic analysis in the ABT papers implies that withdrawal of atrazine would lead to a decrease in corn yields of 4·4% and an increase in corn prices of 8·0%. The result would be an increase in corn growers' revenues, equal to US$1·7 billion annually under ABT assumptions. Price impacts on consumers would be minimal: at current levels of ethanol production and use, gasoline prices would rise by no more than US$0·03 per gallon; beef prices would rise by an estimated US$0·01 for a 4-ounce hamburger and US$0·05 for an 8-ounce steak. Thus withdrawal of atrazine would boost farm revenues, while only changing consumer prices by pennies.